Impact of knowledge management on business innovation of the Santa Catalina Ltda. 103 cooperative in Moquegua 2013. - Zeballos Medina, Nelly Yonny (2020)
Objective: This research was conducted in order to determine the impact of knowledge management in the Business Innovation of the credit union of Moquegua.2013. Method: The research work corresponds to a relational descriptive; and the design is not experimental, transeccional because it came the period 2013. For this purpose the information obtained through the application of the measuring instrument questionnaire was built based on the variables and indicators was considered whose measuring scale was the Likert; which it was applied to sixty workers credit union Santa Catalina of Moquegua. Results: After the phase of analysis and interpretation of the results was determined that the credit union Santa Catalina of Moquegua, knowledge management significantly affects innovation empresarial.2013, proving this way the research hypothesis. Conclusion: In the credit union Santa Catalina of Moquegua, knowledge management empresarial.2013 significant impact on innovation.